Predicting Low Disease State and Remission in Early Rheumatoid Arthritis in the First Six Months, Comparing the Simplified Disease Activity Index and European League Against Rheumatism Response Measures: Results From an Early Arthritis Cohort. Issue 5 (7th April 2017) - Omair, Mohammed A.; Keystone, Edward; Bykerk, Vivian; Lin, Daming; Xiong, Juan; Sun, Ye; Boire, Gilles; Thorne, J. Carter; Tin, Diane; Pope, Janet; Hitchon, Carol; Haraoui, Boulos; et al.
Abstract : Objective: To compare the European League Against Rheumatism (EULAR) and Simplified Disease Activity Index 50% (SDAI50) response measures (RMs) and their impact on future response to treatment in patients with early rheumatoid arthritis (ERA). Methods: Biologic agent–naive ERA patients from the Canadian Early Arthritis Cohort study with complete data at baseline, 3, and 6 months were evaluated. Kappa statistics were used to evaluate the agreement between the EULAR (moderate or good response) and SDAI50 RMs. The RMs at 3 months were also compared for their ability to predict low disease activity state (LDAS) or remission (REM) at 6 months. Results: A total of 1, 124 patients were evaluated. Of those, 215 patients (30%) and 294 patients (45%) failed to achieve a EULAR and SDAI50 response, respectively. There was a good agreement between EULAR and SDAI50 RMs with a kappa of 0.59 (95% confidence interval 0.53–0.66). Throughout the range of disease activity, the SDAI50 response was shown to be more stringent than the EULAR response. Multivariable linear regression analysis demonstrated that both RMs at 3 months were associated with LDAS or REM at 6 months, and SDAI50 had a more significant impact on this outcome compared to the EULAR response. Conclusion: There is a good agreement between the EULAR and SDAI50 RMs. Although a minority of patients have discordant RMs at each end of the disease activity spectrum at baseline, the SDAI50 response at 3 months appears to be a more significant predictor of outcomes at 6 months than EULAR response.